Cross-cultural adaptation and psychometric evaluation of the Yoruba version of Oswestry disability index. - Chidozie Emmanuel Mbada (PLoS ONE, 2020)
INTRODUCTION:Low-Back Pain (LBP) is a common public health problem that is often worsened by maladaptive beliefs and disability. Thus, necessitating the need for availability of outcome measures to assess these sequelae among patients with chronic LBP. This study aimed to cross-culturally adapt and determine the psychometric properties of the Yoruba version of the ODI (ODI-Y). METHODS:The ODI-Y was cross-culturally adapted following the process involving forward translation, synthesis, backward translation, expert review, and pilot testing. Internal consistency and test-retest reliability of the ODI-Y were determined using the Cronbach's alpha and intra-class correlation. Other psychometric properties explored included the factor structure, convergent validity, standard error of measurement and the minimal detectable change. RESULTS:One hundred and thirty-six patients with chronic LBP took part in the validation of the ODI-Y; 86 of these individuals took part in the test-retest reliability (within 1-week interval) of the translated instrument. The mean age of the respondents was 50.5±10.6years. The ODI-Y showed a high internal consistency, with a Cronbach's alpha (α) of 0.81. Test-retest of the Yoruba version of the ODI within 1-week interval yielded an Intra-Class Correlation coefficient of 0.89. The ODI-Y yielded a three-factor structure which accounted for 61.56% of the variance. Correlation of ODI-Y with the visual analogue scale was moderate (r = 0.30; p = 0.001). The standard error of measurement and minimal detectable change of the ODI-Y were 2.0 and 5.5. CONCLUSIONS:The ODI was adapted into the Yoruba language and proved to have good psychometric properties that replicated the results of other obtainable versions. We recommend it for use among Yoruba speaking patients with LBP.